Exploring the Prospects for Islamic Home Finance in the UK: Evidence from the Industry Practitioners’ Perspective - Tanveer Ahmed; Sarkar Kabir; Aqsa Aziz (International Journal of Business and Society, 2020)
The predominant focus of most of the existing literature assessing the potential of Islamic home finance in the UK has been on Muslim customersand also appears to be outdated. This updated study takes a fresh approach, exploring the prospects for Islamic home finance taking into account the UK’s current financial position by involving neglected key stakeholders: independent mortgage consultants. The findings—derived from semi-structured interviews with a sample of ten experienced mortgage brokers—reveal that factors such as affordability (i.e. higher deposits), acceptability (i.e. strict criteria), accessibility (i.e. lack of products and banks),and low levels of product knowledge and recognition have restricted its uptake. The findings also highlight that the Muslim community does not provide a sufficiently large market for Islamic home finance and,as such,it has a limited scope in the UK market.